Determinan Indeks Saham Syariah di Indonesia - Vira Zahroul Agustina; Ris Yuwono Yudo Nugroho (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2022)
The objective of this analysis was to research the effect of macroeconomics on the Indonesian Sharia Stock Index in the long term and short term. The variables of this study are macroeconomic as the independent variable, including Inflation (INF), Exchange Rate (KURS), Policy Interest Rate (SKBI), and Industrial Production Index (IPI). The dependent variable includes the Indonesian Sharia Stock Index. This study uses a quantitative approach. The technique used is the Error Correction Model (ECM). The results showed that INF, KURS, and SKBI had a negative and significant effect on the Indonesia Sharia Stock Index in the long term. In the short term, the exchange rate (KURS) negatively and significantly affects the Indonesian Sharia Stock Index.